PEMBENTUKAN MODEL MANGSA PEMANGSA DENGAN PEMANENAN PADA PEMANGSA - Marom, Saiful (Delta Jurnal Ilmiah Pendidikan Matematika FKIP Universitas Pekalongan, 2013)
The Models of a predator prey with threshold harvesting on the predator is studied in this paper. In this article has established predator prey models with prey-dependent functions and the repon harvesting on predator assuming given. Â Kata Kunci : predator prey models, boundedness of solution, local stability